Fatal and nonfatal railway injuries in eastern Turkiye: evaluation of seventeen years experience - Cavlak, Nevin; Tuerkoglu, Abdurrahim; Tokdemir, Mehmet (Int Assoc Law & Forensic Sciences, 2025)
BackgroundRailway travel is an important route of transport in many countries. In this study, fatal and non-fatal railway-related injuries that occurred over 17 years in a province in eastern Turkey were retrospectively examined in terms of socio-demographic characteristics.ResultsA total of 77 railway-related injuries were evaluated. Of these, 60 (77.9%) were male and 17 (22.1%) were female. The mean age of the victims was 37.48 +/- 17.68 years. Thirty-four of the cases were fatal and 43 were nonfatal injuries. Fatal and non-fatal injuries were most often caused by train-vehicle collisions. Seventy-four (96.1%) of the cases were accidental. The most common type of fatal injuries was head injuries (27 cases); nonfatal injuries were mostly superficial external-only injuries (21 cases). The mortality rate was 44.2%; the highest mortality rate was in the type of incidents involving train-pedestrian collisions (73.7%). The risk of lower extremity amputation increased in train-pedestrian collisions compared to train-vehicle collisions.ConclusionsIt was concluded that measures for the safety of roadway and railway junctions should be increased and precautions should be taken to prevent the access of pedestrians to railway networks.
Keywords: Forensic medicine; Railway injury; Train; Accident; Mortality; Autopsy